Challenges faced by Pakistani undergraduates and views of teachers about the challenges faced by their undergraduates in learning English using the collaborative learning approach (CLA) - Abdul Bari Khan; Joseph Ramanair; Souba Rethinasamay (Penerbit Universiti Kebangsaan Malaysia, 2023)
Though the educational, social, communicative, and practical benefits of the Collaborative Learning Approach (CLA) have been widely examined in past research, very few studies have been conducted to examine the challenges faced by students and teachers in learning English using CLA. This research aimed to investigate the challenges faced by Pakistani undergraduates and their teachers' views about the challenges faced by their undergraduates in learning English using CLA. The study employed a survey design, and data were collected using questionnaires with items adapted from a combination of previous studies. The study involved 420 undergraduates and 35 teachers who were selected through cluster sampling from seven public universities in the federal territory of Pakistan. The findings showed that Pakistani undergraduates showed high views on positive interdependence, whereas moderate views on individual and group accountability, group processing, and face-to-face promotive interaction. On the contrary, undergraduates expressed low views on social skills. Findings from the teachers also correspond with the undergraduates’ views on three elements of CLA, such as positive interdependence, group processing, and face-to face promotive interaction, whereas teachers revealed low views on individual and group accountability and the lowest views on social and interpersonal skills. Overall Pakistani undergraduates have been found to have faced moderate challenges using CLA in learning English. This study describes the challenges that hinder the effective learning of English under CLA for undergraduates that will assist educators, policymakers, and curriculum designers in the development of innovative and useful policies for improving ESL learning.